The glycoprotein mucin‐1 negatively regulates GalNAc transferase 5 expression in pancreatic cancer. Issue 19 (21st July 2019) - Caffrey, Thomas; Sagar, Satish; Thomas, Divya; Lewallen, Michelle E.; Hollingsworth, Michael A.; Radhakrishnan, Prakash
Abstract : Aberrant expression of the glycoprotein mucin‐1 (MUC1) has been associated with pancreatic cancer progression and metastasis as a result of mediating the oncogenic transcriptional regulation of target genes. In the present study, we demonstrate that MUC1 downregulates the expression of the tumor suppressor polypeptide N ‐acetylgalactosaminyltransferase 5 in pancreatic cancer. ChIP‐on‐chip analysis revealed that the MUC1 cytoplasmic tail binds to regulatory elements in the GALNT5 gene. Additionally, MUC1 increases binding of p53 and c‐Jun and decreases the binding of Sp1 to the proximal promoter and exonic regions of GALNT5 . We also observed that expression of N ‐acetylgalactosaminyltransferase 5 is inversionally proportional to MUC1 expression in human pancreatic cancer. These results demonstrate that MUC1 downregulates the expression of N ‐acetylgalactosaminyltransferase 5 in pancreatic cancer by modifying the promoter occupancy of transcription factors through its cytoplasmic domain. Abstract :